Process of IPS Learning Activities in State Primary Schools Asahan District - Hsb, Annisa Rohimah Hasri; Yusnaldi, Eka; Nadia, Nadia; Purba, Liza Saswani; Pane, Mahfuzha; Khadijah, Siti (Continuous Education: Journal of Science and Research, 2023)
The process of social studies learning activities in elementary schools is a learning activity that provides knowledge and develops students' skills in social studies learning and can overcome problems that exist in community life. The learning activities that teachers must carry out must include models, approaches, methods, strategies and techniques as well as tactics in learning. The aim of this research is to find out how the process of social studies learning activities in Asahan Regency Public Elementary Schools is. The method used in this research is a qualitative method with research instruments and interviews. The results of this research indicate that the process of social studies learning activities in state elementary schools involves several aspects of how educators convey social studies knowledge to students, including preparing learning implementation plans (RPP), developing learning strategies and methods according to the material and students' needs as well as assessment tools. social studies subject student learning outcomes. Teachers also need to provide learning resources that are interesting and appropriate to students' needs, such as LKPD and teaching aids, as well as guiding and directing students. Apart from that, implementing cooperative learning can also be an effective method in learning social studies in Asahan district public elementary schools.